Oral cancer prevalence in Western population of Maharashtra, India, for a period of 5 years - Padhiar Rutvij Ajay; S R Ashwinirani; Ajay Nayak; Girish Suragimath; K A Kamala; Abhijeet Sande; Radhika Santosh Naik (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim of this study was to report the prevalence of oral cancer and its association with habits, age, gender, and site in Western population of Maharashtra. Materials and Methods: Data were collected from the previous records of patients from June 2011 to June 2016 for 5 years. A total of 81,325 patients' data were obtained. Details regarding patient's habits, age, gender, and site with OC were recorded. The data recorded were tabulated in the MS Excel and subjected to statistical analysis using SPSS software 16. Data were analyzed using Student's t-test and Chi-square test. Results: The prevalence of OC was 0.1%. The majority of patients were tobacco chewers (41.5%), followed by the group of those who were smokers, tobacco chewers, and alcoholic (28.1%). Majority of patients were in the age group of 60 years and above, followed by 40-59 with a male predominance, and buccal mucosa was the most common site followed by alveolus. Smokeless tobacco consumed in India is one of the most common forms of tobacco, leading to cause OC. Conclusion: There is need to spread awareness about this tobacco-related cancer and immediate consultation on suspicion of cancer. There should be regular oral checkup for male and female patients above 40 years for the early detection of cancer and its prevention.